Asynchronous transfer mode (ATM) real-time applications / Reidzuan Ahmad - Ahmad, Reidzuan (1997)
For this paper, what is meant by real-time in data transmission in the ATM technology for the application such as video and data traffic will be described. It will also determine the bounded time that satisfy the real-time transmission. For that we will look into the congestion-control scheme that will satisfy the trafficdelay requirement. There are many applications that needs a real-time control systems and one of it is a multimedia applications which is integrated of all types of message transmissions. The performance of the multimedia applications and its analysis will be described in this paper. To evaluate the performance, we will designed a model of ATM network using a software COMNET III. Based on the description of the network, its algorithms and workload, COMNET III will simulate the operation of the network performance that support real-time applications